2013
DOI: 10.1371/journal.pone.0066240
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Disturbance and Ecosystem Size Have No Influence on Food Chain Length in Seasonally Connected Rivers

Abstract: The food web is one of the oldest and most central organising concepts in ecology and for decades, food chain length has been hypothesised to be controlled by productivity, disturbance, and/or ecosystem size; each of which may be mediated by the functional trophic role of the top predator. We characterised aquatic food webs using carbon and nitrogen stable isotopes from 66 river and floodplain sites across the wet-dry tropics of northern Australia to determine the relative importance of productivity (indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 86 publications
(184 reference statements)
3
58
1
Order By: Relevance
“…We found that resource availability can explain 60 % of the FCL variation in our studied subtropical rivers, consistent with findings on neotropical (Hoeinghaus et al 2008) and temperate (Thompson and Townsend 2005) rivers. A previous research on Australian wet-dry tropical rivers used nutrient concentration as a measure of productivity, but the results could not explain the relationship between resource availability and FCL (Warfe et al 2013). In the present study, we found that resource availability increased as the river basin area increased and that fish species richness was also positively related to resource availability.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…We found that resource availability can explain 60 % of the FCL variation in our studied subtropical rivers, consistent with findings on neotropical (Hoeinghaus et al 2008) and temperate (Thompson and Townsend 2005) rivers. A previous research on Australian wet-dry tropical rivers used nutrient concentration as a measure of productivity, but the results could not explain the relationship between resource availability and FCL (Warfe et al 2013). In the present study, we found that resource availability increased as the river basin area increased and that fish species richness was also positively related to resource availability.…”
Section: Discussioncontrasting
confidence: 93%
“…Although productivity generally increases FCL (Thompson and Townsend 2005;Hoeinghaus et al 2008;Doi 2012), the effects of the magnitude of ecosystem size could positively (Post et al 2000;Takimoto et al 2008;Doi et al 2009;McHugh et al 2010;Sabo et al 2010) or neutrally (Thompson and Townsend 2005;Warfe et al 2013) influence FCL. Furthermore, the effects of disturbance on FCL are highly variable and could be positive (Calizza et al 2012), neutral (Walters and Post 2008;Warfe et al 2013), or even negative (McHugh et al 2010;Sabo et al 2010).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have found conflicting effects of ecosystem size, productivity, and disturbance on food-chain length (Takimoto and Post 2013; Warfe et al. 2013). However, in most studies, the identity of the top predator has changed across these gradients.…”
Section: Introductionmentioning
confidence: 99%